PROCESSING USED COOKING OIL INTO AN ENVIRONMENTALLY FRIENDLY PRODUCT AS A CREATIVE ECONOMIC SOLUTION - Yuniar; Anerasari M; Didiek Hari Nugroho; Erika Dwi Oktaviani; Zareena Rosli (RADJA PUBLIKA, 2025)
Used cooking oil (UCO) from institutional kitchens poses environmental and health risks if improperly disposed of. This community programme, jointly organised by Politeknik Negeri Sriwijaya and Politeknik Malaysia Merlimau, aimed to introduce a simple method for converting UCO into solid soap, an eco-friendly and economically valuable product. The activity employed an applied mixed-methods design, comprising pre-assessment, technical training, hands-on practice, and post-evaluation. Participants learned about UCO purification, saponification, and safe handling of NaOH. Results indicate a substantial increase in participants’ knowledge and awareness, with 100% of respondents demonstrating improved understanding of UCO hazards and soap-making procedures. Practical implementation was successful, yielding approximately 150 bars of solid soap during the workshop. All participants expressed willingness to continue soap production independently due to its low cost, environmental benefits, and potential for micro-enterprise. The programme demonstrates that simple, community-based technical interventions can effectively enhance practical competence and promote sustainable waste valorisation. This model shows strong potential for replication in similar educational and community settings.